PROTECTING THE RIGHT TO IDENTITY AGAINST CATFISHING: WHAT’S THE CATCH? - Ndyulo, Lisa (Obiter, 2023)
Catfishing is a common social media phenomenon affecting a person’s right to identity. It involves using a person’s image without their consent to create a fake social media profile. Catfishing has legal implications because a person’s image is a facet of the right to identity and using an image without a person’s consent interferes with their right to identity and dignity. While catfishing is a novel legal issue in South Africa, courts and legislators in the United States (US) have addressed catfishing. In the US states of California and Oklahoma, catfishing is tackled through statutory interventions directed at online impersonation and catfishing. Accordingly, victims of catfishing have remedies in addition to the existing causes of action related to common-law torts and breaches of the right to publicity. This comparative study analyses the remedies available to US victims of catfishing to ascertain whether South African victims have adequate statutory and common-law remedies against catfishing, to protect their identity from interference with their subjective right, and from assaults to their dignity.